Prognostic value of subclinical atherosclerosis in patients with a SCORE risk <5%: data from a 10-year follow-up - M. D. Smirnova; O. A. Pogorelova; T. V. Fofanova; O. N. Svirida; Z. N. Blankova; M. I. Tripoten; B. M. Tamaeva; E. B. Yarovaya; F. T. Ageev; T. V. Balakhonova (Российский кардиологический журнал)
Aim. To evaluate the contribution of subclinical atherosclerosis to the stratification of patients with a SCORE risk of cardiovascular events (CVEs) <5% based on a 10-year follow-up.Material and methods. The study included 379 patients with SCORE risk of CVEs <5% (82 men, 297 women). In 2009, all patients underwent clinical examination, carotid artery (CA) ultrasound with the detection of plaques, total CA occlusion, intima-media thickness (IMT) of the common carotid artery (CCA). The plaque number was determined as the total number of all plaques in 6 following segments: both CCAs, both CCA bifurcations and both internal carotid arteries. The total stenosis was calculated as the sum of stenoses in 6 CA segments in %. In 2019, a telephone survey of patients was conducted with a questionnaire assessing the following CVEs: all-cause death, cardiovascular death, myocardial infarction (MI), stroke, myocardial revascularization, cardiovascular hospitalizations, and composite endpoint.Results. The initial patients’ age ranged from 35 to 67 years (51,1±7,5 years). Plaques from 20% to 50% were detected in 303 participants (79,94%). Over the past 10 years, there have been 5 cardiovascular deaths (1,3%), 7 MIs (1,8%), 5 cases of unstable angina (1,3%), 12 cases of myocardial revascularization (3,2%), 15 strokes (4,0%), 51 cardiovascular hospitalizations (13,5%). The proportion of patients with registered endpoints (CVE+) was 22,4% (n=85). The groups of patients with and without CVEs differed in the level of systolic blood pressure (BP) and blood triglycerides, and did not differ in the level of diastolic BP, lipid profile, glucose, heart rate, smoking status, sex, and age. In the CVE+ group, there were higher values of CCA IMT (0,65 (0,64; 0,70) mm vs 0,62 (0,62; 0,66) mm, p<0,05), total CA stenosis (102,5 (88,1; 120,8)% vs 80 (72,5; 88,1)%, p=0,01), and the CA plaque amount (4,0 (2,8; 3,9) vs 3,0 (2,6; 3,1), p=0,01), respectively. Total CA stenosis was an independent predictor of CVEs when adjusted for sex, age, systolic and diastolic BP (β=0,149; p<0,05), but not for lipid profile. A ROC-analysis revealed a cut-off point for total CA stenosis of 82,5% (AUC=0,598, 95% confidence interval 0,5243-0,673, p<0,05).Conclusion. The total CA stenosis has shown itself to be an independent predictor of CVEs in patients with a SCORE risk <5%.